Práticas pedagógicas libertárias no ensino de geografia: o viés libertário do estudo do meio na escola moderna nº1 e nº2 de São Paulo - Ramos, Hudson Alberto Rosa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research conducted to obtain Geography course graduation title, is turned to the education field, more specifically the teaching learning process, it has the purpose to study the methodologies of interdisciplinary work among the libertarian schools - those created in the I and II Modern School in the 1910s, respectively, engaged in the manufacturing space-São Paulo context. For this purpose was delimited in the case study and research object the objectives to be pursued - ranging from the rescue of the theoretical framework proposed by the anarchist geographers Peter Kropotkin and Élisée Reclus, showing the relationship of their ideas and their involvement with the assumptions of rationalist education, created by the Spanish educator Francisco Ferrer y Guardia - through analysis of digitized historical materials of the time. The purpose is to show the importance of libertarian bias of the Milieu Studies for Geography teaching, which have recently been recognized by today's references because throughout the twentieth century, the theoretical formulations of the theme of the Milieu Studies have changed and been retrofitted to the educational context of their times. After these steps, we analyze the production of materials created in these spaces, which were shared in these schools, with insertion in unions of various crafts and cultural centers, according to the defined space-cut as these libertarian practices provided historical experiences involving cultural and political literacy and educational background to the recent Brazilian working class

Esta pesquisa, realizada para obtenção de título de graduação do curso de Geografia, destina-se à área de Educação e mais especificamente ao Ensino, tem como proposta estudar as metodologias de trabalho interdisciplinar, dentre as escolas libertárias - aquelas criadas na Escola Moderna I e II, na década de 1910, respectivamente, encaixadas no contexto espaço-temporal fabril paulistano. Para tanto, delimitou-se no estudo de caso e objeto de pesquisa, os objetivos a serem buscados - que vão desde o resgate dos referenciais teóricos propostos pelos geógrafos anarquistas Piotr Kropotkin e Élisée Reclus, mostrando a relação de suas ideias e envolvimento destes com as premissas da educação racionalista, criadas pelo pedagogo espanhol Francisco Ferrer y Guardia - por meio de análise de materiais históricos digitalizados da época. A finalidade é mostrar a importância do viés libertário dos Estudos do Meio para o ensino de Geografia, que foram ultimamente reconhecidos por referências da atualidade, pois a longo do século XX, as formulações teóricas da temática dos estudos do meio modificaram-se e foram readaptadas ao contexto educacional de suas épocas. Depois destas etapas, analisa-se a produção de material criada nesses espaços, que eram compartilhadas nessas escolas, com inserção em sindicatos de ofícios vários e centros culturais, segundo o recorte espaço-temporal definido, pois estas práticas libertárias proporcionaram experiências históricas que envolviam alfabetização e formação educacional, cultural e política à recente classe operária brasileira
Keywords: Geografia - Estudo e ensino; Escolas; Anarquismo e anarquistas